Diplomacy for Development: Key to Sustaining Democratic Transformation - Bhattarai, Dinesh (NCWA Annual Journal, 2023)
Foreign policy has a great bearing on a country’s sovereign and independent status as well as overall development. For a country like Nepal sitting in a highly sensitive geopolitical location between China and India that are becoming major global powers, a whole of government approach integrating into itself a coherent, consistent, and credible economic policy alone produces a sovereign and independent foreign policy. No policy works in isolation. Correct communication, coordination, and collaboration between government departments and ministries are essential for any policy to succeed and be effective at home and abroad. The strength of the country abroad comes from strength at home. For a country like Nepal diplomacy stands as its tool of first and last resort. Economic strength is the key to national strength and comprehensive national power. The following paragraphs discuss the close connection between socio-economic transformation and political transformation, and past efforts made to promote economic diplomacy. The moment there appears a disconnect between managing geopolitics and speeding the process of economic transformation, the country becomes a fertile ground for geopolitical play. The write-up towards the end puts up some suggestions to make diplomacy for developing effective and result oriented for the country’s development.